Effect of Adeninesulphate on Organogenesis Via Leaf Culture in An Ornamental Plant: Thevetia Peruviana (Pers.) Schum - GARIMA ZIBBU; AMLA BATRA (International Journal of Pharma and Bio Sciences, 2010)
The paper presents protocol for rapid, reliable and high frequency regeneration of plant via the culture of leaf explants in Thevetia peruviana (Pers.) Schum. In vivo leaves cultured on MS medium supplemented with a combination of 2,4-D (2.5 mg/l) and Kn (1.2 mg/l) produced stock callus after 20-28 days of inoculation. The obtained callus was dark green and friable. The small pieces of stock callus cultured on MS medium fortified with 2,4-D (2.0 mg/l), Kn (1.0 mg/l) and AdSO4 (0.25 mg/l) for the morphogeneic responses. After 30 days of incubation period, emergence of 3-4 microshoots from the callus was observed. Multiple shoots separated from the cluster and subcultured for their elongation on the same medium used for the multiplication along with BAP (3.0 mg/l). In vitro elongated shoots rooted on MS medium supplemented with IBA (0.5 mg/l). The plantlets were hardened, acclimatized and transplanted in the field, where they showed 60% survival rate.